Analisis dan Perancangan Sistem Informasi Customer Relationship Management (CRM) berbasis Web pada Sekolah Dasar Islam Terpadu (SDIT) Al Muthmainnah - Suroto, Suroto; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2019)
The current form of customer relationship at the Sekolah Dasar Islam Terpadu (SDIT) Al Muthmainnah has not optimally held interaction with customers, therefore the SDIT Al Muthmainnah requires a Customer Relationship Management (CRM) system. This research aims to analyze and design a web-based CRM at SDIT Al Muthmainnah. With the System Development Life Cycle (SDLC) method, this research only discusses the first 3 stages of SDLC; system investigation, system analysis, and system design. The design of the CRM model used is the Strategic Framework for CRM. The system of modeling sets used is UML (Unified Modeling Language). The result of this research is prototype of webbased CRM at SDIT Al Muthmainnah that can improves the quality of customer relationships. This research can be further developed into a mobile-based CRM system, integrated with the Sistem Informasi Akademik (SIAKAD), and make adjustments to the level of education other than elementary school.